The Effect of Dividend Policy, Debt Policy, and Profitability on Firm Value (An Empirical Study of Manufacturing Companies in the Consumer Non-Cyclical Sector Listed as ISSI Stocks) - Galuh Putri; Dick Marbun; Parulian Butarbutar (Penerbit Jurnal Indonesia, 2026)
This study aims to analyze the effect of dividend policy, debt policy, and profitability on firm value in consumer non-cyclical sector companies listed in the Indonesia Sharia Stock Index (ISSI) during the 2018–2022 period. Firm value is proxied by the company’s book value, while dividend policy is measured using the Dividend Payout Ratio (DPR), debt policy is measured using the Debt to Asset Ratio (DAR), and profitability is measured using Return on Assets (ROA). This research employs a quantitative approach with an associative research design to examine the relationships and effects among variables. The data used in this study are secondary data obtained from officially published annual financial statements. The population consists of all consumer non-cyclical sector companies listed on the Indonesia Stock Exchange, with a sample of 16 companies selected through purposive sampling based on predetermined criteria. Data analysis was conducted using panel data regression with the assistance of EViews 10 software. Model selection was performed through the Chow test, Hausman test, and Lagrange Multiplier test, supported by classical assumption tests and hypothesis testing. The results indicate that, partially, dividend policy and debt policy do not have a significant effect on firm value. In contrast, profitability as measured by ROA has a positive and significant effect on firm value. These findings suggest that a company’s ability to generate profits from its assets is a key factor considered by investors in assessing sharia-based consumer non-cyclical sector companies. This study is expected to contribute to the development of sharia financial literature and to provide practical insights for investors and corporate management in making financial decisions.